INTERNALISASI NILAI-NILAI MULTIKULTURAL MELALUI BUDAYA ORGANISASI DI SEKOLAH MENENGAH ATAS ISLAM - Desi Novita Sari (Jurnal Adab dan Peradaban Islam, 2025)
This study examines the process of internalizing multicultural values through organizational culture in Islamic Senior High Schools within the context of Indonesia’s social diversity. The background of this research is the importance of developing students’ character to be tolerant and respectful of differences through a conducive school culture. The aim of the study is to analyze the mechanisms of internalizing multicultural values, the role of organizational culture, as well as the supporting and inhibiting factors in the process. The research employed a qualitative phenomenological approach involving principals, teachers, and students from three Islamic Senior High Schools in West Java. Data were collected through in-depth interviews, participant observation, and document analysis over a period of eight months. The findings indicate that multicultural values are internalized through organizational culture, including school rituals, inclusive leadership, social interactions, and role modeling. The study concludes that a strong organizational culture serves as an effective medium for internalizing multicultural values in shaping a tolerant and moderate generation.